Catch-up cycle: A general equilibrium framework - Peilin Liu; Jia Shen; Xun Zhang (Asian Development Bank Institute (ADBI), 2017)
Certain stylized facts are common among successful economic latecomers: an inverse U-shaped gross domestic product and capital per capita growth rate, high growth rates during the catch-up period, and rapid structural changes. This paper, for the first time, proposes a general equilibrium framework to document the catch-up cycle that a successful latecomer is likely to experience. We argue that technology adoption and imitation, and the diminishing marginal returns to capital are the two driving forces of the catch-up cycle. The technological gap and speed/efficiency of technological catching-up are two fundamental factors for successful catching-up. This paper concludes with a case study for the People's Republic of China and sheds light on the different policy choices in various stages of the catch-up cycle.
Keywords: E13; E60; O11; 330; Economics; China; People's Republic of